Potensi Kulit Kacang Tanah (Arachis hypogaea) Sebagai Sumber Karbon Untuk Material Maju - Rida Rida; Umar Kalmar Nizar (Jurnal Periodic Jurusan Kimia UNP, 2023)
Carbon material is one example of the development of advanced materials. Carbon is the result of the decomposition of an organic compound through an imperfect carbonization process. Carbon can be utilized from organic waste materials containing cellulose, hemicellulose, lignin and starch. The composition of peanut shells is 65.7% cellulose, the high content of cellulose in peanut shells makes it a potential carbon source. The method used for the manufacture of peanut shell carbon is calcination at various temperatures of 250 0C, 300 0C, 350 0C and 400 0C. Carbon proximate analysis was carried out by testing the ash content, vapor content and bound carbon content. In this study the standard used is SNI 06-3730-1995. The results of the analysis showed that the ash content increased with increasing calcination temperature, while the vapor content decreased with increasing calcination temperature. The carbon content obtained decreases with increasing calcination temperature. The optimum condition of peanut shell carbon close to SNI 06-3730-1995 was obtained at carbon with a calcination temperature of 250 0C, 5.10% and a vapor content of 7.41% and a bound carbon content of 87.49%.